2001
DOI: 10.1034/j.1600-0854.2001.20804.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Highly Divergent Nuclear Export Signals Can Regulate Export by the Competition for Transport Cofactors in Vivo

Abstract: Nucleo-cytoplasmic transport of proteins is mediated by nuclear export signals, identified in various proteins executing heterologous biological functions. However, the molecular mechanism underlying the orchestration of export is only poorly understood. Using microinjection of defined recombinant export substrates, we now demonstrate that leucine-rich nuclear export signals varied dramatically in determining the kinetics of export in vivo. Thus, nuclear export signals could be kinetically classified which cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…However, the fact that both CSR and stability require maintenance of key hydrophobic positions in the NES and show a similar dependence on the identity of the interdigitating hydrophilic residues suggests that they might both depend on the quality of the AID-exportin interaction. Changes in the hydrophilic interdigitating amino acids in an NES have been shown in other systems to affect the quality of exportin-binding and kinetics of intracellular transport (20,21). The dependence of CSR and protein stability on the nature of the NES could therefore simply reflect a requirement for particular kinetics of nucleocytoplasmic shuttling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that both CSR and stability require maintenance of key hydrophobic positions in the NES and show a similar dependence on the identity of the interdigitating hydrophilic residues suggests that they might both depend on the quality of the AID-exportin interaction. Changes in the hydrophilic interdigitating amino acids in an NES have been shown in other systems to affect the quality of exportin-binding and kinetics of intracellular transport (20,21). The dependence of CSR and protein stability on the nature of the NES could therefore simply reflect a requirement for particular kinetics of nucleocytoplasmic shuttling.…”
Section: Discussionmentioning
confidence: 99%
“…18 The NES mediates the RanGTP-dependent Crm1 interaction, is conserved in all mammalian survivin proteins 19 and matches the consensus sequence for leucine-rich NESs. 20 In particular, microinjection of recombinant GST-GFP fusion proteins proved to be a highly reliable and stringent system that allows the quantification of transport in living cells independent of drug treatment or passive diffusion. 11 Microinjection experiments revealed that although the NES proposed by Colnaghi et al 21 ( 96 LTLGEFLKL 104 ) partially overlaps with the NES identified by us, this signal is not sufficient to mediate effective export (manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…The putative NES (aa 95À103 ) loosely fits a consensus sequence proposed by, Heger et al 16 L-x(2,3)-(FILVMP)-x(2)-(LI)-x-(LIV). Furthermore, COILS algorithms indicate the typical COOHterminal coiled-coil conformation (aa 127À147 ), usually present in survivin but missing in other IAP family members.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies in which chromosome region maintenance 1-mediated, NES-dependent nuclear export of human survivin was blocked by LMB. 10,16 Survivin is a subunit of the chromosomal passenger complex (CPC), consisting of Aurora-B, Borealin and INCENP, and is essential for proper Conserved dual role of survivin B Luthringer et al chromosome segregation and cytokinesis. As Crm1 is involved in tethering the CPC to the centromere by interacting with survivin's NES, 10 SDSURVL might affect various stages of cell proliferation, from proper kinetochore attachment to spindle formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation